Dynamic phase measurement of fast liquid crystal phase modulators - Fells, JAJ; Salter, PS; Welch, C; Jin, Y; Wilkinson, TD; Booth, MJ; Mehl, GH; Elston, SJ; Morris, SM (Optica Publishing Group, 2022)
We present dynamic time-resolved measurements of a multi-pixel analog liquid crystal phase modulator driven at a 1 kHz frame rate. A heterodyne interferometer is used to interrogate two pixels independently and simultaneously, to deconvolve phase modulation with a wide bandwidth. The root mean squared optical phase error within a 30 Hz to 25 kHz bandwidth is <0.5° and the crosstalk rejection is 50 dB. Measurements are shown for a custom-built device with a flexoelectro-optic chiral nematic liquid crystal. However, the technique is applicable to many different types of optical phase modulators and spatial light modulators.